Association of sitting time and physical activity with musculoskeletal and cardiovascular health in industrial workers - Fernandes, Marta Isabel Gomes (2022)
Background: The levels of sedentarism have been increasing among developed countries, especially during work, as heavy jobs have been performed by machinery and administrative and office jobs started to grow. Low levels of physical activity (PA) are associated with all-cause and cardiovascular disease (CVD) mortality, cancer, and diabetes and a higher prevalence of musculoskeletal disorders (MSD). Purpose: Analyze the levels of PA and time spent in sedentary behaviors and its association with the prevalence of work-related musculoskeletal symptoms and CVD risk factors in industrial workers. The secondary objective was to compare PA levels, sedentary behaviors, musculoskeletal symptoms, and CVD risk factors between men and women. Methods: This is a cross-sectional observational study. Participants were recruited from an industrial factory and were eligible if they worked in the company for 2 years or more. The participants completed a questionnaire, including socio-demographic data, clinical history, characteristics of their workstations, and working schedules. Diet habits were assessed through the Mediterranean Diet Adherence Screener (MEDAS), PA was assessed using the International Physical Activity Questionnaire (IPAQ) – Short Form, and musculoskeletal symptoms with the Nordic Musculoskeletal Questionnaire. Body weight, height, waist circumference, and blood pressure were measured. Results: A total of 79 (43 male and 36 female) workers with a mean age of 38.8 ± 10.9 years participated in the study. The most prevalent CVD risk factor was family history of CVD (34.2%). Most of them showed moderate (68.4%) or good (25.3%) adhesion to the Mediterranean diet. The participants worked a mean of 5.0 ± 0.4 days (41.5 ± 6.3 hours) per week, mostly sitting (86.1%), and performing repetitive movements with the upper arm and hand (e.g., computer mouse, screwing) (44.3%). They spent 34.0 ± 11.5 hours per week in sedentary behavior (sitting time) during work and 19.6 ± 16.0 hours during their leisure time. The most common body regions with musculoskeletal symptoms in the last 12 months were the neck (56.6%), lumbar spine (51.3%), shoulder (47.4%), and wrist/hand (31.6%). Forty participants (50.6%) reported doing active breaks (3.4 ± 1.9 pauses/day and 4.7 ± 3.4 minutes of duration per pause). Leisure sitting time associated with thoracic symptoms (p=0.004, r2=0.333). Regarding PA, 35.6% showed low, 35.6% moderate, and 28.8% high levels; 43.8% reported walking more than 3 times a week. Low levels of PA were related to neck symptoms (p=0.054, χ2=5.8) and wrist/hand symptoms (p=0.054, χ2=5.9). Men did two times more vigorous activities than women (p=0.024). When adjusting for PA, women showed higher intensity of symptoms in the shoulder (p=0.012) and knee (p=0.047). Women reported doing more repetitive movements with the upper arm and hand (p=0.018), but there were no significant differences between men and women in musculoskeletal symptoms. Conclusion: A high prevalence of musculoskeletal symptoms among industry workers was observed; the body regions most affected were the neck, lumbar spine, shoulder, and wrist/hand. The neck and wrist or hand symptoms showed a significant relationship with low levels of PA. No evidence was found that sitting at work is more of a risk factor for symptoms than leisure sitting time alone. Women are more likely to report wrist/hand symptoms than men.